Moss species and precipitation mediate experimental warming stimulation of growing season N2 fixation in subarctic tundra - Lett, Signe; Christiansen, Casper T.; Dorrepaal, Ellen; Michelsen, Anders (Global change biology, 2024)
Climate change in high latitude regions leads to both higher temperatures and more precipitation but their combined effects on terrestrial ecosystem processes are poorly understood. In nitrogen (N) limited and often moss‐dominated tundra and boreal ecosystems, moss‐associated N2 fixation is an important process that provides new N. We tested whether high mean annual precipitation enhanced experimental warming effects on growing season N2 fixation in three common arctic‐boreal moss species adapted to different moisture conditions and evaluated their N contribution to the landscape level. We measured in situ N2 fixation rates in Hylocomium splendens, Pleurozium schreberi and Sphagnum spp. from June to September in subarctic tundra in Sweden. We exposed mosses occurring along a natural precipitation gradient (mean annual precipitation: 571–1155 mm) to 8 years of experimental summer warming using open‐top chambers before our measurements. We modelled species‐specific seasonal N input to the ecosystem at the colony and landscape level. Higher mean annual precipitation clearly increased N2 fixation, especially during peak growing season and in feather mosses. For Sphagnum‐associated N2 fixation, high mean annual precipitation reversed a small negative warming response. By contrast, in the dry‐adapted feather moss species higher mean annual precipitation led to negative warming effects. Modelled total growing season N inputs for Sphagnum spp. colonies were two to three times that of feather mosses at an area basis. However, at the landscape level where feather mosses were more abundant, they contributed 50% more N than Sphagnum. The discrepancy between modelled estimates of species‐specific N input via N2 fixation at the moss core versus ecosystem scale, exemplify how moss cover is essential for evaluating impact of altered N2 fixation. Importantly, combined effects of warming and higher mean annual precipitation may not lead to similar responses across moss species, which could affect moss fitness and their abilities to buffer environmental changes. In tundra ecosystems, future climate will be warmer and wetter, but the combined effects are uncertain. Bacteria can fix new nitrogen in these nitrogen‐limited areas. We found that warming did not change nitrogen fixation much in common moss species, while more rain increased it. Surprisingly, warming reduced nitrogen fixation in dry mosses in rainier places. Wet Sphagnum moss colonies had the highest nitrogen fixation rates, but drier feather mosses added more nitrogen overall because they cover more ground. Therefore, the type and amount of moss will influence how much nitrogen is added to tundra under future climate change.